Quantitative Detection for Porphyromonas gingivalis in Tooth Pocket and Saliva by Portable Electrochemical DNA Sensor Linked with PCR. Issue 12 (17th November 2014) - Yamanaka, Keiichiro; Sekine, Shinichi; Uenoyama, Takahiro; Wada, Masahiro; Ikeuchi, Tomohiko; Saito, Masato; Yamaguchi, Yoshinori; Tamiya, Eiichi
Abstract Here, a quantitative electrochemical analysis of periodontal bacteria in gingival crevicular fluid (GCF) and saliva by direct polymerase chain reaction (PCR) is presented. The electrochemical measurement was performed by mixing with PCR products and electrochemical indicator (bisbenzimidazole trihydrochloride). The peak current of indicator is reduced due to slower diffusion when the dye intercalates into the amplified DNA, and the degree of reduction in the peak current is correlates with the quantity of amplified DNA. Therefore, a quantitative analysis is possible by using our electrochemical method at the end point of PCR. In the GCF testing, The number of Porphyromonas gingivalis (Pg) detected by our electrochemical method at the end point of PCR were almost same compared with that were calculated by the conventional method of quantitative realtime PCR. In the saliva testing, the relationship between number of Pg in saliva and average pocket depth, and age‐dependence were also clearly observed. Since the saliva sample is obtained in a non‐invasive manner, this method is useful for the primary screening of periodontal disease. Moreover, our detection method is simple and uses a hand‐held potentiostat making it suitable for development of an on‐site periodontal diagnosis system.